Loot / A novel - James, Tania (New York : Alfred A. Knopf, 2023)
"Abbas is just seventeen years old when he leaves his family to serve in the court of Tipu Sultan, a volatile and unpredictable ruler. An inspired woodcarver, Abbas is apprenticed to a master toy maker in order to build a massive tiger automaton, a gift to celebrate the return of the Sultan's sons from British captivity. Working alongside the legendary French clockmaker Monsieur du Leze, Abbas hones his craft and learns to read French and then meets Jehane, the daughter of one of du Leze's fellow expatriats. When du Leze is finally permitted to return home to Paris, he begs Abbas to accompany him. But by the time Abbas travels to Europe, the palace has been looted by British forces, and the tiger automaton disappears. To prove himself and make a livelihood in Paris-with the lovely Jehane at his side-Abbas must retrieve the tiger from an estate in the English countryside, where it is displayed in a collection of plundered Moorish and Oriental Art"--
Keywords: India -- History -- 18th century -- Fiction; France -- History -- 1789-1900 -- Fiction; Novels